Effect of corticotrophin on formaldehyde-induced somatostatin of spinal cord in rats - Wu Qiang; Li Xi-cheng; Ruan Huai-zhen; Li Hai-di; Zhao Bang-yun (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of corticotrophin (Cor) on somatostatin (Som) and its synthesis in spinal dorsal horn induced by formaldehyde in rats. METHODS: Using double immunohistochemical stainings, and in situ hybridization. RESULTS: Two hours after s.c. formaldehyde (5%, 200 microL) in one hindpaw of rats, the neurons of c-fos-like immunoreactivity (FLI), somatostatin-like immunoreactivity (Som-LI), Som-LI/FLI, and perprosomatostatin mRNA (PPS-mRNA) in ipsilateral spinal dorsal horn were increased obviously, as compared with the control group. The FLI and Som-LI of spinal cord were not changed by i.p. Cor. Cor (25 or 12.5 U.kg-1, i.p.) inhibited the formaldehyde-evoked FLI, Som-LI, Som-LI/FLI, and PPS-mRNA of spinal cord in a dose-dependent manner. The decrease of c-fos or Som level due to i.p. Cor in rats of chronic pain was prevented by raphe nuclei injected cyproheptadine, but not by bicuculline, naloxone, or phentolamin injected to raphe nuclei. CONCLUSION: The formaldehyde-evoked c-fos expression, Som, and Som synthesis of spinal cord were suppressed by Cor through the serotonin receptor of raphe nuclei.